A CBN dispersion-reinforced tool steel composite material and its preparation method and application

By using mechanical alloying and discharge plasma sintering technology, a nano-CBN dispersion-reinforced tool steel composite material was prepared, which solved the problems of bonding strength and wear resistance of the stirring head during high-temperature welding, and improved the high-temperature strength and service life of the stirring head.

CN116397151BActive Publication Date: 2025-01-10FUNIK ULTRAHARD MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211700489.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-01-10
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

Existing stirring heads exhibit weakened mechanical properties and decreased wear resistance when welding low-melting-point alloys at high temperatures, leading to frequent wear and breakage. Furthermore, CBN particles have difficulty bonding with the tool steel matrix, resulting in the propagation of microcracks during the welding process.

Method used

Tool steel powder and catalyst materials are mechanically alloyed, and nano-cubic boron nitride is uniformly mixed. Then, nano-CBN microcrystals are formed by discharge plasma sintering technology, which promotes the metallurgical bonding between CBN and the tool steel matrix, and improves the bonding strength and material density.

Benefits of technology

This technology enables the stirring head material to exhibit excellent wear resistance and high-temperature strength during high-temperature welding, thereby extending the service life of the stirring head and reducing the risk of wear and breakage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a CBN dispersion reinforced tool steel composite material and a preparation method and application thereof, belonging to the field of metallurgical composite materials. The preparation method comprises the following steps: (1) subjecting tool steel powder and catalyst material to mechanical alloying treatment to obtain pre-treated alloy powder; (2) uniformly mixing nano cubic boron nitride with the pre-treated alloy powder to obtain a mixture, and then subjecting the mixture to discharge plasma sintering to obtain a tool steel composite material. The nano CBN dispersion reinforced tool steel material obtained by the preparation method has very few voids and a large nano CBN grain density, so that the tool steel has better plasticity, excellent wear resistance and high high temperature strength, thereby improving the life of the processed stirring head and tool.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a CBN dispersion reinforced tool steel composite material and a preparation method and application thereof, belonging to the field of metallurgical composite materials. Background Art

[0002] Traditional mixing heads are mainly made of tool steel, which is low in cost, easy to process, has good comprehensive performance and high cost performance. The working of the mixing head is to generate heat and plastic deformation of the metal through friction and stirring with the workpiece, so the material used to make the mixing head should have good wear resistance and high temperature resistance, etc. In addition, the mixing head material is also required not to chemically react with the workpiece at any temperature.

[0003] When using friction stir welding (FSW) technology to weld aluminum alloys and magnesium alloys with lower melting points, the interface temperature between the stirring head and the workpiece can reach a high temperature of about 500°C. Therefore, when using a stirring head to weld aluminum alloys, the mechanical properties of the tool steel will gradually weaken and the wear resistance will decrease due to the welding thermal cycle. When welding thin aluminum alloys, serious wear and fracture will occur within a few hundred meters; when welding thick plates, the stirring head is subjected to greater force and has a shorter lifespan, and the welding tool needs to be replaced frequently.

[0004] Cubic boron nitride (CBN) has a hardness second only to diamond, and has excellent wear resistance, thermal stability and chemical inertness, making it very suitable for preparing stirring head materials. However, as an inert material, cubic boron nitride has very stable chemical properties and very low surface free energy. If the stirring head material is directly sintered from CBN powder and tool steel powder, the interface bonding between CBN particles and tool steel matrix is ​​difficult. The concentrated distribution of voids in the sintered body at the grain boundary causes a weak connection between CBN and the matrix, and microcracks are easily generated during high-temperature welding. The expansion of these microcracks is an important reason for the fracture and low life of the stirring head. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a CBN dispersion reinforced tool steel composite material, so as to solve the problems of fracture and short service life of a stirring head during high temperature welding in the prior art.

[0006] The second object of the present invention is to provide a CBN dispersion reinforced tool steel composite material, so that the tool steel has better plasticity, excellent wear resistance and higher high temperature strength.

[0007] The third object of the present invention is to provide an application of a CBN dispersion reinforced tool steel composite material.

[0008] In order to achieve the above objectives, the technical solution adopted by the preparation method of the CBN dispersion reinforced tool steel composite material of the present invention is:

[0009] A method for preparing a CBN dispersion reinforced tool steel composite material comprises the following steps:

[0010] (1) subjecting tool steel powder and catalyst material to mechanical alloying treatment to obtain pretreated alloy powder;

[0011] (2) The nano cubic boron nitride is uniformly mixed with the pretreated alloy powder to obtain a mixture, and then the mixture is subjected to spark plasma sintering to obtain a tool steel composite material.

[0012] The present invention firstly alloys tool steel powder and catalyst material to form a solid solution, obtains alloy powder with fine particles and fine structure, and makes the catalyst material evenly distributed in the alloy matrix, then evenly mixes the alloy powder with nano cubic boron nitride, promotes the melting and recrystallization of cubic boron nitride through the catalytic effect of the catalyst material, and then generates dispersed nano-sized CBN microcrystals in the alloy matrix, which has a strengthening effect on the alloy strength, and finally sintering is performed to obtain the tool steel composite material.

[0013] Under the conditions of plasma sintering process, the sintering temperature is low, the sintering time is short, and a fine and uniform structure can be obtained, which can improve the strength and hardness of the material without reducing the plasticity and toughness of the material. In addition, during the sintering process, the layer of CBN structure where the nano-CBN contacts the molten catalyst metal is transformed into active elements. As the sintering continues, these elements nucleate and grow continuously, thus forming an interface that is metallurgically bonded with the tool steel matrix material, and at the same time, it will not have a significant impact on the plasticity of the tool steel.

[0014] Therefore, the nano-CBN dispersion-reinforced tool steel material prepared by the preparation method has very few voids and a larger nano-CBN grain density, so that the tool steel has better plasticity, excellent wear resistance and higher high-temperature strength.

[0015] Preferably, the molar percentage of the catalyst material in the pretreated alloy powder in step (1) is 3-5%.

[0016] Preferably, the particle size of the tool steel powder is 10-100 μm. The tool steel powder within this particle size range can more fully contact with the catalyst material, thus promoting uniform distribution of the catalyst material in the tool steel powder.

[0017] Preferably, the catalyst material is one or a mixture of lithium, magnesium and calcium. These three catalyst materials can catalyze the growth of cubic boron nitride and promote the melting and recrystallization of CBN microcrystals.

[0018] Preferably, the molar percentage of nano cubic boron nitride in the mixture in step (2) is 10-20%. The sum of the molar percentages of nano cubic boron nitride and pretreated alloy powder in the mixture is 100%.

[0019] Preferably, the sintering pressure of the spark plasma sintering is 30-100 MPa, and the sintering temperature is 1000-1500° C. The use of spark plasma sintering is conducive to reducing the sintering temperature of the mixed powder, and low voltage and high current can make the mixed powder sinter quickly and densely.

[0020] Preferably, the spark plasma sintering time is 20 to 50 minutes.

[0021] The technical solution adopted by the CBN dispersion reinforced tool steel composite material of the present invention is:

[0022] A CBN dispersion reinforced tool steel composite material is prepared by adopting the above preparation method.

[0023] The technical solution adopted in the application of the CBN dispersion reinforced tool steel composite material of the present invention is:

[0024] The invention discloses an application of a CBN dispersion reinforced tool steel composite material. The CBN dispersion reinforced tool steel composite material can be used to manufacture a stirring head and a cutting tool for stir friction welding.

[0025] The stirring head made of the CBN dispersion-reinforced tool steel composite material is wear-resistant and has good welding performance. DETAILED DESCRIPTION

[0026] The present invention firstly mixes tool steel powder and catalyst material by mechanical alloying method to obtain pre-treated alloy powder; specifically, the mixing is carried out by ball milling, the ball milling speed is 300-400r / min, the ball-to-material mass ratio is (8:1)-(10:1), 5-10% anhydrous ethanol is used as liquid ball milling medium, and the pre-treated alloy powder is sieved after ball milling, and the mesh number of the inspection sieve is 325 meshes, so as to obtain the pre-treated alloy powder.

[0027] Then the obtained pre-treated alloy powder is mixed with nano cubic boron nitride in a certain proportion to obtain a mixture, wherein the molar percentage of nano cubic boron nitride in the mixture is 10-20%, and the sum of the pre-treated alloy powder and the nano cubic boron nitride is 100%, and vacuum drying is performed at a drying temperature of 50-80°C and a drying time of 8-12 hours. Finally, the mixture is spark plasma sintered at a synthesis pressure of 30-100 MPa and a synthesis temperature of 1000-1500°C to obtain a nano CBN dispersion reinforced tool steel composite material.

[0028] The technical solution of the present invention is further described below in conjunction with specific implementation methods.

[0029] 1. The specific embodiment of the preparation method of the CBN dispersion reinforced tool steel composite material of the present invention is as follows:

[0030] Example 1

[0031] The preparation method of the CBN dispersion reinforced tool steel composite material of this embodiment adopts the following steps:

[0032] (1) Tool steel powder (W18Cr4V) and lithium powder are used to prepare alloy powder. The particle size of the tool steel powder ranges from 30 μm to 50 μm, the molar percentage of lithium powder in the alloy powder is 3%, and the particle size of the lithium powder ranges from 50 to 80 μm. The tool steel powder and lithium powder are ball milled by mechanical alloying method, wherein the ball milling speed is 300 r / min, the ball-to-material mass ratio is 8:1, and 5% anhydrous ethanol is added as the ball milling medium.

[0033] After the ball milling is completed, the ball-milled alloy powder is taken out from the vacuum glove box and passed through a 325-mesh inspection sieve to obtain a pretreated alloy powder.

[0034] (2) Nano cubic boron nitride and pretreated alloy powder are mixed in a molar ratio of 10:90, wherein the particle size of the nano cubic boron nitride is 50 to 100 nm. After being evenly mixed, vacuum drying is performed at a drying temperature of 60°C and a drying time of 10 h. Then, spark plasma sintering is performed at a synthesis pressure of 30 MPa, a synthesis temperature of 1500°C and a sintering time of 20 min to obtain a nano CBN dispersion reinforced tool steel composite material.

[0035] Example 2

[0036] The preparation method of the CBN dispersion reinforced tool steel composite material of this embodiment adopts the following steps:

[0037] (1) Tool steel powder (W18Cr4V) and magnesium powder are used to prepare alloy powder. The particle size of the tool steel powder ranges from 70 μm to 100 μm, the molar percentage of magnesium powder in the alloy powder is 5%, and the particle size of the magnesium powder ranges from 30 to 50 μm. The above metal powders are ball milled by mechanical alloying method, the ball milling speed is 350 r / min, the ball-to-material mass ratio is 10:1, and 7% anhydrous ethanol is added as liquid ball milling medium.

[0038] After the ball milling was completed, the alloy powder was taken out from the vacuum glove box and passed through a 325-mesh inspection sieve to obtain a pretreated alloy powder.

[0039] (2) Nano cubic boron nitride and pretreated alloy powder are mixed in a molar ratio of 20:80, wherein the particle size of the nano cubic boron nitride is 50-100 nm. After being evenly mixed, they are vacuum dried at a drying temperature of 80°C and a drying time of 8 hours. Then, spark plasma sintering is performed at a synthesis pressure of 100 MPa, a synthesis temperature of 1250°C and a sintering time of 40 minutes to obtain a nano-CBN dispersion-reinforced tool steel composite material.

[0040] Example 3

[0041] The preparation method of the CBN dispersion reinforced tool steel composite material of this embodiment adopts the following steps:

[0042] (1) Tool steel powder (W18Cr4V) and calcium powder are used to prepare alloy powder. The particle size of the tool steel powder is 10-20 μm, the molar percentage of calcium powder in the alloy powder is 3.5%, and the particle size of the calcium powder is 40-70 μm. The above metal powders are ball milled by mechanical alloying method, the ball milling speed is 400 r / min, the ball-to-material mass ratio is 8:1, and 10% anhydrous ethanol is added as liquid ball milling medium.

[0043] After the ball milling was completed, the alloy powder was taken out from the vacuum glove box and passed through a 325-mesh inspection sieve to obtain a pretreated alloy powder.

[0044] (2) Nano cubic boron nitride and pretreated alloy powder are mixed in a molar ratio of 16:84, wherein the particle size of the nano cubic boron nitride is 50 to 100 nm. After being mixed evenly, the mixture is vacuum dried at a drying temperature of 50°C and a drying time of 12 h. Then, spark plasma sintering is performed at a synthesis pressure of 75 MPa, a synthesis temperature of 1000°C and a sintering time of 50 min to obtain a nano CBN dispersion reinforced tool steel composite material.

[0045] The CBN dispersion reinforced tool steel composite material of the present invention is obtained by the preparation method of Examples 1-3.

[0046] 2. Comparison

[0047] Comparative Example 1

[0048] The preparation method of the CBN dispersion reinforced tool steel composite material of this comparative example adopts the following steps:

[0049] Cubic boron nitride and tool steel powder (W18Cr4V) were uniformly mixed in a mass ratio of 10:90 and then subjected to spark plasma sintering, wherein the synthesis pressure was 30 MPa, the synthesis temperature was 1500° C., and the sintering time was 20 min to obtain a comparative composite material.

[0050] Comparative Example 2

[0051] The preparation method of the CBN dispersion reinforced tool steel composite material of this comparative example adopts the following steps:

[0052] Cubic boron nitride and metal powder (including tool steel powder and lithium powder) are mixed in a mass ratio of 10:90, with the molar percentage of lithium powder in the metal powder being 3% and the particle size range being 50-80 μm. After being evenly mixed by ball milling, spark plasma sintering is performed with a synthesis pressure of 30 MPa, a synthesis temperature of 1500°C and a sintering time of 20 min to obtain a comparative composite material.

[0053] 3. Experimental Example Application of CBN Dispersion Reinforced Tool Steel Composites

[0054] Experimental Example 1: Sample hardness measurement

[0055] In this experimental example, the hardness of the tool steel composite materials prepared in Examples 1-3 and Comparative Examples 1-2 was measured.

[0056] Specifically, the blanks synthesized in Examples 1-3 and Comparative Examples 1-2 were ground and polished into standard samples, and their Rockwell hardness was further measured. The results are shown in Table 1.

[0057] Table 1

[0058] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Rockwell hardness 65.8 69.3 67.4 50.2 59.8

[0059] It can be seen from Table 1 that compared with Comparative Example 1, the hardness of the standard samples obtained by the preparation methods of Examples 1-3 is increased by more than 31%, and compared with Comparative Example 2, the hardness of the standard samples obtained by the preparation methods of Examples 1-3 is increased by more than 10%. The hardness of the standard samples obtained by the present invention is higher, indicating that the presence of the catalyst material promotes the in-situ generation of dispersed CBN microcrystals by melting and recrystallization, improves the interface bonding strength between CBN and the tool steel matrix material and the sintered density, thereby improving the strength of the sample.

[0060] Experimental Example 2 Welding Test

[0061] In this experimental example, welding tests were performed on the tool steel composite materials prepared in Examples 1-3 and Comparative Examples 1-2, as well as conventional tool steel materials.

[0062] According to the shape of the stirring head, the tool steel material is processed into a stirring head, and then a welding test is carried out on the friction stir welding machine. The welding object is a magnesium alloy plate with a thickness of 5mm. During welding, the rotation speed of the stirring head is controlled to be 1000rpm and the forward speed is 30mm / min.

[0063] After testing, the nano-CBN dispersion-reinforced tool steel stirring heads prepared in Examples 1-3 showed no obvious wear and cracks after the linear welding length exceeded 870 m, while the comparative composite material stirring heads prepared in Comparative Example 1 showed obvious wear and cracks after the linear welding length was 495 m, the comparative composite material stirring heads prepared in Comparative Example 2 showed obvious wear and cracks after the linear welding length was 574 m, and the conventional tool steel material stirring heads showed obvious wear and deformation after the linear welding length was 231 m.

[0064] It can be seen that the presence of the catalyst material promotes the melting and recrystallization of nano-CBN microcrystals, making the stirring head have excellent wear resistance and high high-temperature strength, thereby increasing the life of the stirring head.

Claims

1. A method for preparing a CBN dispersion reinforced tool steel composite material, characterized in that: The following steps are involved: (1) Mechanically alloying tool steel powder and catalyst material to obtain pretreated alloy powder; (2) uniformly mixing the nano cubic boron nitride with the pretreated alloy powder to obtain a mixture, and then performing spark plasma sintering on the mixture to obtain a tool steel composite material; The molar percentage of the catalyst material in the pretreated alloy powder in step (1) is 3-5%; the catalyst material is one of lithium, magnesium and calcium; the molar percentage of nano cubic boron nitride in the mixture in step (2) is 10-20%.

2. The method for preparing the CBN dispersion reinforced tool steel composite material according to claim 1, characterized in that: The particle size of the tool steel powder is 10-100 μm.

3. The method for preparing the CBN dispersion reinforced tool steel composite material according to claim 1, characterized in that: The sintering pressure of the spark plasma sintering is 30-100 MPa, and the sintering temperature is 1000-1500°C.

4. The method for preparing the CBN dispersion reinforced tool steel composite material according to claim 3, characterized in that: The spark plasma sintering time is 20 to 50 minutes.

5. A CBN dispersion reinforced tool steel composite material, characterized in that: The composite material is prepared by the preparation method of the CBN dispersion reinforced tool steel composite material as claimed in any one of claims 1 to 4.

6. An application of the CBN dispersion reinforced tool steel composite material as claimed in claim 5, characterized in that: The CBN dispersion-reinforced tool steel composite material is used for manufacturing a stirring head and a cutting tool for stir friction welding.

Citation Information

Patent Citations

  • Preparation method of strength and plasticity matched nano carbon reinforced titanium-based composite material

    CN110625124A

  • Cubic boron nitride composite ceramic tool and production thereof

    JP1996239277A